Carpal Tunnel Syndrome and Related Median Neuropathies : Challenges and Complications - Duncan, Scott F. M.; Kakinoki, Ryosuke (Springer International Publishing : Imprint: Springer, 2017)
Practical and user-friendly, this text provides the orthopedic and hand surgeon with all the essential information for diagnosing and treating carpal tunnel syndrome (CTS) and other median neuropathies of the hand and wrist, with special emphasis on challenges and complications. Organized to allow for easy searching of specific subject matter, opening chapters discuss anatomy of the median nerve, history and pathophysiology of CTS, clinical presentation and diagnosis, including imaging, and severity scoring. Presentation of various treatment strategies follows, both non-operative and surgical, including open and endoscopic techniques and revision surgery, incomplete release, transection, use of the reverse radial forearm flap, vein wrap, synovial wrap, and microneurolysis. Other median neuropathies are discussed as well, including neuromas and stimulation for chronic median nerve pain. Generously illustrated, Carpal Tunnel Syndrome and Related Median Neuropathies is a valuable resource for orthopedic and hand surgeons on the evaluation and treatment of complications and complexities arising from carpal tunnel syndrome and surgery.
Keywords: Medicine.; Rheumatology.; Orthopedics.; elektronické knihy; electronic books